(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of Working Capital Turnover (WCT) and Current Ratio (CR) on Return on Assets (ROA) at PT Mulia Industrindo Tbk for the period 2016–2024. The study uses a quantitative approach with an associative research type. The data used are secondary data obtained from the company’s annual financial statements. The research sample was determined using a purposive sampling technique and resulted in 9 observations during the period 2016–2024. Data analysis was carried out using multiple linear regression using statistical software, which began with classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. Furthermore, hypothesis testing was carried out through a t-test to determine the partial effect and an F-test to determine the simultaneous effect of independent variables on the dependent variable. The results of the study indicate that Working Capital Turnover (WCT) and Current Ratio (CR) partially do not have a significant effect on Return on Assets (ROA). In addition, the results of the simultaneous test indicate that WCT and CR also do not have a significant effect on ROA. This finding indicates that company profitability is more influenced by other factors beyond the effectiveness of working capital turnover and the company’s liquidity level.